2
$\begingroup$

I am trying to find the sum of the following series:

$$\sum_{n=1}^{\infty} {\frac{1+7^n}{9^n}}$$

which I rewrote as

$$\sum_{n=1}^{\infty} \left(\frac{1}{9^n}+ \left(\frac{7}{9}\right)^n\right)$$

I am assuming that it is a geometric series and the initial value is

$$a_1=\frac{1}{9} + \frac{7}{9}$$

I also see that

$$a_2 = \frac{1}{9^2} + \frac{7^2}{9^2}$$

I know that in a geometric series the first term is $a$ and the second term is $ar$.

This allows me to see that

$$\left(\frac{1}{9}+\frac{7}{9}\right)r=\frac{1}{9^2}+\frac{7^2}{9^2}$$

which when solved for $r$ gives the value $\frac{25}{36}$.

Using the formula to find the sum of a geometric series $\frac{a}{1-r}$, I find that the sum is equal to $\frac{32}{11}$.

But this value is incorrect and the sum is actually $\frac{29}{8}$. How does one find that value?

$\endgroup$
  • 1
    $\begingroup$ It is not a geometric series. But you can express it as the sum of two geometric series: $\Sigma_n 1/9^n$ and $\Sigma_n 7^n/9^n.$ $\endgroup$ – mfl Nov 5 '14 at 0:33
  • $\begingroup$ Remember that $a^n+b^n\neq(a+b)^n$, I think that was what confused you. $\endgroup$ – David Nov 5 '14 at 6:59
6
$\begingroup$

This is not a geometric series.

But it is the sum of two geometric series:

$$\sum_{n=1}^{\infty} {\frac{1+7^n}{9^n}} = \sum_{n=1}^{\infty} {\frac{1}{9^n}}+ \sum_{n=1}^{\infty} {\frac{7^n}{9^n}} =\frac 19 \frac 1{1-\frac 19} +\frac 79\frac 1{1-\frac 79}$$

because $$ \left|\frac 19\right|<1 \\\left|\frac 79\right|<1 $$

$\endgroup$
  • 2
    $\begingroup$ The sums start at $n=1$ not $n=0$ making the formula for geometric series different. $\endgroup$ – coffeemath Nov 5 '14 at 0:35
  • $\begingroup$ @coffeemath oh right, thanks! $\endgroup$ – mookid Nov 5 '14 at 0:36
  • $\begingroup$ Beat me too it. $\endgroup$ – Dair Nov 5 '14 at 0:38
2
$\begingroup$

Hint: Try re-doing it as two separate series, $\sum(1/9)^n$ and $\sum(7/9)^n.$ The first has first term $1/9$ and common ratio $1/9$ while the second has first term $7/9$ with common ratio $7/9.$

$\endgroup$
0
$\begingroup$

$$ \frac{\frac19}{1-\frac19}+\frac{\frac79}{1-\frac79}=\frac18+\frac72=\frac{29}{8}. $$

$\endgroup$
  • $\begingroup$ is this really helpful? $\endgroup$ – mookid Nov 5 '14 at 0:36
  • $\begingroup$ @mookid Something must be left to OP's own work... $\endgroup$ – Przemysław Scherwentke Nov 5 '14 at 0:39
  • 3
    $\begingroup$ I don't think this is the tricky part. $\endgroup$ – mookid Nov 5 '14 at 0:40
0
$\begingroup$

\begin{align*}\sum_{n=1}^\infty\frac{1+7^n}{9^n} &= \sum_{n=1}^\infty\bigg[ \frac{1}{9^n} + \frac{7^n}{9^n}\bigg] \\ &= \sum_{n=1}^\infty\frac{1}{9}\bigg(\frac{1}{9}\bigg)^{n-1} + \sum_{n=1}^\infty \frac{7}{9}\bigg(\frac{7}{9}\bigg)^{n-1} \\ &=\frac{1}{9}\bigg(\frac{1}{1-\frac{1}{9}}\bigg)+\frac{7}{9}\bigg(\frac{1}{1-\frac{7}{9}}\bigg) \\ &= \frac{1}{8}+\frac{7}{2} \\ &= \frac{29}{8} \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.